A study the Population Development of Schedule Tribes, Literacy Rate & Family Planning Schemes of Jharkhand State: Exploring the Relationship between Population, Tribal Culture, and Development in Jharkhand State (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The word Jharkhand was coined to give a cognitive value to the tribal land of Chotangpur andsanthal Pargana of Bihar. Once the cognitive role of Jharkhand was settled, later it was thought thatJharkhand must comprise of its adjoining areas of Madhya Pradesh, Orissa and West-Bengal. Over aperiod of time, the name „Jharkhand‟ gained popularity across the land and tribes gradually developed ofa feeling of respect for the name „Jharkhand‟. Jharkhand state in India is basically administrative and forimplementation of measures to control the rapid increase in population which create problem in thedevelopment of our country as well as the state.The adivasis of the Chotanagpur region (Jharkhand)were motivated to define their own independent state by the government's anti-tribal policies. STs areindigenous to the area, get their own distinct culture, are geographically isolated, live in poverty. Theprimary goal is to improve the overall standard of living for all people. Birth control is a scientificallyproven way for a couple to regulate their family size, and this fact is emphasized in family planning.